Feasibility of a randomised controlled trial of two types of written information for people with knee osteoarthritis. Issue 2 (June 2022) - Darlow, Ben; Brown, Melanie; Hudson, Ben; Frew, Gareth; Clark, Jane; Vincent, Loren; Abbott, J.Haxby; Briggs, Andrew M.; Grainger, Rebecca; Marra, Carlo; McKinlay, Eileen; Stanley, James
Abstract: Objective: Test the feasibility of conducting an individually randomised controlled trial recruiting people with knee osteoarthritis (OA) in community pharmacies and evaluate the impacts of a novel information booklet. Design: People with knee OA were identified by pharmacy staff using clinical criteria and randomised to receive a novel information booklet (intervention) or the currently available written OA resource (active control). Mixed-methods process evaluation assessed participant recruitment, retention, and experience. Participant-reported outcome measures, assessing OA illness perceptions, OA knowledge, fear of movement, and pain when walking at baseline and 4-weeks, were analysed using linear regression models (adjusted for baseline). Results: Of 72 eligible people, 64 were randomised to intervention (n ​= ​33) or control (n ​= ​31). The randomisation sequence was followed correctly and no protocol deviations identified. Mean recruitment rate was 2.7 participants per pharmacy per week. One-in-five participants had no educational qualifications and one-in-four had not received a knee OA diagnosis prior to the trial. Three meta-themes emerged from pharmacist and participant qualitative analysis: 'pleased to be asked'; 'easy process'; and 'successful process'. Three participants were lost to follow-up. At 4 weeks, intervention arm Knee Osteoarthritis Knowledge Scale scores improved (mean difference ​= ​3.6, 95%CI 0.7 to 6.5). Brief Illness Perceptions Questionnaire scores were similar between groups (mean difference 0.4, 95%CI -3.7 to 4.5). Conclusion: It is feasible to conduct an individually randomised trial in community pharmacy, a potentially effective setting to initiate accessible OA care. A novel information booklet improved OA knowledge, but is unlikely to affect illness perceptions on its own.